ANALISIS EXPERT SYSTEM DIAGNOSIS PENYAKIT OBESITAS PADA ORANG DEWASA MENGGUNAKAN BACKWARD CHAINING METHOD - Aulia Hayani Lubis (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this study is to build an expert system for diagnosing obesity in adults using the PHP programming language and MySQL database, the backward chaining method is suitable to be applied to the diagnosis of an expert system for diagnosing obesity in adults using PHP and MySQL so that it can be accessed online by users and implementation the backward chaining method on an expert system can help diagnose obesity in adults and provide solutions quickly and accurately. The research method used is qualitative using the backward chaining method. It is hoped that the result of this study is that an expert system for diagnosing obesity in adults with the Backward Chaining method can provide information about the symptoms and solutions of the disease and can be used at any time and does not require a long time to diagnose. This system can help doctors work and make it easier for the public to diagnose obesity in adults and their prevention efforts.